Pregnancy outcome in women with intrahepatic cholestasis of pregnancy - Kant, Shashi; Attri, Sumeet; Thakur, Sita; Sood, Ajay (International Journal of Research in Medical Sciences, 2020)
Background: Intrahepatic cholestasis of pregnancy is a multifactorial condition of pregnancy diagnosed when otherwise unexplained pruritus with abnormal liver function test and neither of which has an alternative cause. The most appropriate gestational age for the delivery of women with ICP is yet to be determined. The present study is designed to determine whether with active intervention, pregnancy with ICP can be carried to a later gestation. Methods: Fifty Women with diagnosed a case of ICP were recruited into the study. The diagnosis of ICP was based on the symptoms, clinical examination and lab investigations. Group I: 25 women planned for delivery at POG 37 - 37+6 weeks of pregnancy. Group II: 25 women Planned for delivery at POG ≥38 weeks of pregnancy. Results: In group, one woman had preterm delivery at POG 36+2 weeks and rest of 24 women were delivered at POG 37-37+6 weeks. In group II, out of 25 women one woman had emergency LSCS at POG 35+3 weeks for MSL and induction of labour was done in 2nd for abnormal fetal well-being tests at POG 37 weeks. One woman had pre-term delivery at POG 36+1 weeks. Remaining 22 women in group II were delivered at POG ≥38 weeks. In the present study there was no significant difference in the gestational age at delivery between the two groups. Conclusions: It can be concluded that pregnancies with obstetric cholestasis can be carried to later gestation of ≥38 weeks under surveillance with UDCA treatment.